Characterization of Alkali-Activated Palm Oil Fuel Ash Pastes as a Function of Calcination Temperatures of Raw Precursor - Flora, Albert Daud; Idawati, Ismail; Raudhah, Ahmadi; Nur Amalina Shairah, Abdul Samat (ASTM International, 2020)
This research investigates the influence of calcination temperatures of palm oil fuel ash (POFA) on the properties of the raw precursor and its hardened binder after alkali activation.The raw POFA obtained from palm oil mill is treated at 500°C, 600°C, and 700°C for approximately 6 h. The treated POFA (TPOFA) is characterized for particle size distributions and chemical compositions by X-ray fluorescence (XRF); microstructural properties by observing through scanning electron microscopy (SEM); and Fourier-transform infrared spectroscopy (FTIR) for molecular functional groups. Pastes of alkali-activated POFA (AAPOFA) are synthesized with 12 M sodium hydroxide (NaOH) as alkali activator where the liquid to binder ratio is 0.4. Calcination temperatures are observed to have some influences on the physical properties (such as color, texture, particle size and fineness) and chemical properties (such as composition and reactivity) of the raw precursor. These properties control microstructural evolution of hardened pastes, compressive strength and capillary sorptivity properties of the hardened pastes. Overall results show 500°C is the optimum calcination temperature for POFA that contributes to comparable strength and lowest permeability of AAPOFA binders.